Description of the province of Atacama (Bolivia) in 1832 - Téllez Lúgaro, Eduardo; Silva Galdames, Osvaldo (Cuadernos de Historia, 2013)
It is presents a document indicating the road routes in the province of Atacama and its connections with villages located in territories belonging to Bolivia, Chile and Argentina, indicating the distances between them and theirs geographical and economic landscapes.